Wuhan strain of SARS-CoV-2 triggers activation of immune evasion machinery similar to the one operated by cancer cells - Abooali, Maryam; Yasinska, Inna M.; Thapa, Gauri; Lei, Xi; da Costa, Kelly A. S.; Schlichtner, Stephanie; Berger, Steffen M.; Fasler-Kan, Elizaveta; Temperton, Nigel J.; Vuono, Romina; Sumbayev, Vadim V. (Frontiers in Immunology, 2025)
In the last 2 years, there has been an increasing concern that SARS-CoV-2 infection may represent a marker of undiagnosed cancers. A potential connection between COVID-19/long COVID and malignant transformation/cancer progression was reported in a number of studies. It is, however, unclear if the virus itself can cause malignant transformation or if it has a potential to support malignant processes in human body. We analyzed nasopharyngeal swabs collected from individuals infected with Wuhan strain of SARS-CoV-2 and conducted in vitro studies using BEAS-2B human bronchial epithelial cells. Here we report that Wuhan strain of SARS-CoV-2 and its spike protein induce activation of hypoxia-inducible factor 1 (HIF-1) transcription complex in infected cells. This effect is achieved through conversion of cellular 2-oxoglutarate into 2-hydroxy-glutarate, which most likely blocks the activity of HIF-1α prolyl hydroxylation. As such, it leads to activation of HIF-1, which triggers production of transforming growth factor–β type 1 (TGF-β). TGF-β induces expression of immune checkpoint proteins, such as galectin-9, programmed death-ligand 1, and indoleamine-2,3-dioxygenase, an enzyme, which is involved in production of immunosuppressive amino acid called L-kynurenine. These immune checkpoint pathways were capable of suppressing both helper and cytotoxic activities of T lymphocytes and, as such, could potentially support malignant processes in infected tissues.